Sustainable bioremediation techniques for mitigating marine pollution in maritime operations - Meilinasari Nurhasanah Hutagaol; Ferro Hidayah (University of Muhammadiyah Malang, 2025)
Marine pollution from oil spills, vessel discharges, and ballast water poses significant challenges to environmental sustainability and maritime operations. This research explores the potential of bioremediation techniques, focusing on oil-degrading microorganisms, biofilters, bioreactors, and marine plants, to address these issues. By integrating biological and environmental engineering, the study evaluates the effectiveness and adaptability of these methods for maritime applications. Using a qualitative methodology, data were collected through interviews with 13 maritime professionals, 24 educators, and 33 graduates, supplemented by thematic analysis and technical evaluations. The findings highlight the high effectiveness of oil-degrading microorganisms in hydrocarbon degradation, the adaptability of biofilters and bioreactors for wastewater and ballast water treatment, and the dual ecological and pollution mitigation benefits of marine plants. Stakeholder collaboration and the integration of bioremediation into maritime education emerged as critical enablers for advancing these technologies. The research concludes that bioremediation offers scalable, sustainable solutions for mitigating marine pollution, contributing to environmental compliance, ecosystem restoration, and operational efficiency in the maritime industry. These findings provide actionable insights for technology integration, policy development, and capacity building, supporting the maritime sector’s transition toward sustainability.